Analysis of the skilled work force effect on the logistics performance index—case study from India - Amrita Jhawar; S. K. Garg; Shikha N. Khera (Logistics Research, 2014)
The purpose of this paper is to study the impact of development of skilled work force through investment in training, welfare, working conditions, and wages on the logistics performance index. It also discusses the effect of skilled labour on logistics cost, logistics time, reliability, flexibility, and safety of a logistics system. The paper is based on a case study conducted on an Indian Logistics Service provider. A causal loop diagram and the stock and flow diagram have been developed according to system dynamics modelling principles. The simulation result shows significant improvement in the logistics performance index. The reduction in logistics cost and logistics time is 12 % and 80 min, respectively. With training provided to 36 % employees of the company, the retention rate improved by 58 % and score of recruitment reached to 4.4 out of five. The paper shows that investment done in human resources in the Indian logistics sector will help the logistics service providers and their customers in terms of improved logistics performance and higher profits and will also improve the image attractiveness of the Indian logistics industry.
Keywords: 650; Human resources; Indian logistics industry; Logistics performance index; System dynamics; Causal loop diagram